Auditoría de Gestión a la Unidad Educativa Padre Julián Lorente de la ciudad de Loja, periodo 2021. - Cárdenas Carreño, Dayanna Alejandra (2023)
The curricular integration work called: Management audit of the Unidad Educativa Padre Julian Lorente de la ciudad de Loja, period 2021, was developed to evaluate the internal control carried out by the educational establishment based on current legal regulations. the degree of fulfillment of the activities and the optimal management of resources. To carry out the work, the Management Audit Manual issued by the Contraloría General del Estado was taken as a reference to apply methods and procedures that allowed the proposed objectives to be achieved and to meet all the phases that the management audit implies; starting with the preliminary knowledge where the preliminary visit was made to gather information, later the planning was carried out to analyze and process the information collected, design the risk matrix, define the focus and reason for the audit. Continuing with the Execution phase, the procedures established in the Audit Program were applied and the internal control of the campus was evaluated, where the main findings were obtained; the nonobservance of current legal regulations for public sector entities, the lack of staff training, the possible risks are not evaluated, there are no physical verifications of the resources it possesses. Likewise, management indicators were applied to determine the efficiency and effectiveness of the activities carried out, which were described in the analytical certificates. Then, the communication of results was carried out, and a final audit report was developed, including comments, conclusions, and recommendations for each of the components examined. To end the audit process, the Follow-up phase continued, where the activities required to meet the recommendations were detailed through a schedule.